Influential Article Review - Understanding How Trade Coordination Affects Innovation - Cohen, Phyllis; Briggs, Mack (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines technological innovation. We present insights from a highly influential paper. Here are the highlights from this paper: Based on the theory of technology spillover in international trade, this paper discusses the technological innovation effect of trade by taking the influence of domestic trade into account. Under the constraint of the production possibility frontier, there is either complementarity or substitutability between domestic and foreign trade. It must be decided whether resources should be concentrated in one of the sectors (trade specialization) or instead allocated equally (trade equalization) between the two sectors. This paper firstly discusses how domestic trade and foreign trade work together to influence technological innovation, and how trade equalization and specialization affect different types of innovation. Using a provincial-level panel dataset from 2007 to 2015 in China, this paper constructs the indicators of domestic and foreign trade linkage and examines the impact of trade on innovation. The findings show that trade equalization mainly promotes incremental innovation, while trade specialization improves radical innovation. Thus, in the area of incremental innovation, attention should be paid to the equalized development of domestic and foreign trade, while in areas pursuing radical innovation, emphasis should be put on the specialization of the trade sector, avoiding equal allocation of resources to the two sectors. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.